Controlled Natural Language Second International Workshop, CNL 2010, Marettimo Island, Italy, September 13-15, 2010. Revised Papers - Rosner, Michael; Fuchs, Norbert E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Second International Workshop on Controlled Natural Language, CNL 2010, held in Marettimo Island, Italy, in September 2010. The 9 revised papers presented in this volume, together with 1 tutorial, were carefully reviewed and selected from 17 initial submissions. They broadly cover the field of controlled natural language, stressing theoretical and practical aspects of CNLs, relations to other knowledge representation languages, tool support, and applications.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Text processing (Computer science; Translators (Computer programs).; Computer Science; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Language Translation and Linguistics; Information Systems Applications (incl. Internet).; Document Preparation and Text Processing